The Manor House - Macmillan, Gilly (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2023)
When her husband Tom is found dead, Nicole, whose life has been forever changed after a massive lottery win, finds her dream world turning into a nightmare, realizing that big money can bring big problems and big threats, making her wonder if Tom's death was really a tragic accident-and if she's next.
New Book Winter 2023.
Keywords: Murder -- Fiction; Lottery winners -- Fiction; Couples -- Fiction; Man-woman relationships -- Fiction; Murder -- Investigation -- Fiction; Death threats -- Fiction; Husbands -- Fiction -- Death; Gloucestershire (England) -- Fiction; Novels; Thriller fiction; Psychological fiction